Examining financial controls practices among religious non-profit organisations: a case study of Malaysia - Rozaidy Mahadi; Noor Kaziemah Sariman; Lee, Andy Chen Hiung (Macrothink Institute, 2021)
There have been many financial scandals associated with religious-based non-profit organisations (RNPOs), their involvement in unethical and wrongdoing has pressured non-profit organisations, especially religious-based NPOs (RNPOs) to start adopting highly transparent and accountable financial management practices. Despite many efforts to improve the RNPOs’ service quality, their integrity has been tinted with many scandalous incidents of funds embezzlement and corruption. Poor financial accountability and lack of legal requirements are argued to be the underpinning reasons for such financial atrocities occurring. With the absence of sound financial governance and comprehensive financial regulations, it has been impaired the government’s ability to detect, prevent and correct RNPOs’ financial misconduct. To prevent financial misconduct from repeatedly occurring, having cogent financial control practices will ensure the RNPOs upholding their accountability duties to the clients they have served. Therefore, the objective of this paper is to examine Malaysian RNPOs financial controls practices. In doing so, various religious-based NGOs’ (i.e. Islam, Buddha, and Christian) representatives were interviewed, analysed, and appraised with Simon’s (1994) control framework. The findings indicate that the RNPOs financial control practices are mediated by the virtue of the religions that they have adopted, the RNPOs’ affiliation (i.e. local-based, foreign-based, and/or semi-government organisation), and the level of sponsorships and grants they have received.